Development of a Library Automation System Using SLIMS in the Department of Curriculum & Educational Technology, Padang State University - Asshiddiq, Affan; Zen, Zelhendri; Novrianti, Novrianti; Hendri, Nofri (JUPE : Jurnal Pendidikan Mandala, 2025)
Development of a Library Automation System Using SLiMS in the Department of Curriculum & Educational Technology, Padang State University. In the current digital era, university libraries are expected to be able to adapt to developments in information and communication technology. An ideal library should be able to provide fast and easy access to information resources, whether in print or digital form. Meanwhile, the fact found in the field is that there are still many libraries that still use manual systems in library management. One of them is the library of the Department of Curriculum & Educational Technology, Padang State University. This of course causes various problems. Therefore, this research aims to develop a library management system that was previously manual into a library automation system using SLiMS 9 Bulian software. This type of research is R&D using the fourD (4D) model. This research consists of 4 stages, namely: definition, design, development and dissemination. The system validity test was carried out by two system experts from lecturers at the Department of Curriculum & Educational Technology, Padang State University. Practicality tests are carried out for literacy unit administrators and library users. Based on the system expert validator's assessment, an average percentage result was obtained of 92% with the criteria "Very valid". The practicality test results obtained an average score of 4.75 in the "Very Practical" category.